An interactive e-learning system for improving web programming skills - Elgamal, A. F.; Abas, H. A.; Baladoh, E.-S. M. (Education and information technologies, 2013)
This paper introduces an interactive e-learning system that provides an integrated environment for web programming. The proposed system is web-based. It provides an online editor for writing, editing, updating, and executing programming code, so the learners can execute examples and practical exercises online. In addition, it provides auto complete and syntax highlighting in editing code, which could help learners to remember the syntax more easily. The proposed system provides communication and interactive tools including Chat-Room, E-Mail, and Discussion Board (Forum) among learners and instructors. Moreover, it provides the instructors with an online exam system. It monitors, collects and keeps information about learners’ performance and activities. Therefore, instructors can use the recorded information to keep tracking of the learner’s progress. The system is based on the common three-tier-architecture of web-based applications that is organized into presentation tier, logic tier, and data tier.